EFFICACY OF SURGICAL SPERM RETRIEVAL IN AZOOSPERMIC PATIENT AND ITS CONTRIBUTION TO IN VITRO RERTILIZATION PROGRAM - Gde Sanjaya, I Putu; Birowo, Ponco; Rasyid, Nur; Sini, Ivan Rizal; Wiweko, Budi (Indonesian Urological Association, 2015)
Objective: This study was made to evaluate efficacy and success rate of Percutaneous Epididymal Sperm Aspiration (PESA), Microsurgical Epididymal Sperm Aspiration (MESA), or Testicular Sperm Extraction (TESE) in azoopsermic patients, and evaluate IVF program’s pregnancy rate by comparing methods of sperm retrieval. Material & method: A descriptive retrospective study to azoospermic patients undergone PESA, MESA or TESE and IVF program in Bunda Hospital Jakarta and Cipto Mangunkusumo Hospital Jakarta in 2011–2012. The data were collected from patients’ medical records and IVF program’s database. Results: There were 146 azoospermic patients with mean age 38.97 ± 7.35 years. Viable sperm was found in 46 patients (31.5%) by PESA and 47 patients (32.2%) by MESA and TESE. The IVF program was followed by 72 patients. Sperm was retrieved by PESA in 43 patients (59.7%) and TESE in 29 patients (40.3%). Pregnancy was achieved in 18 patients in PESA group (25%) and 15 patients (20.8%) in TESE group. Conclusion: Sperm can be retrieved from azoospermic patients by PESA, MESA or TESE, and there was good success rate in pregnancy rate of IVF program by using surgically retrieved sperm.